Mechanism of medical hemorrhoid gel in relieving pruritus ani via inhibiting the activation of JAK2/STAT3 pathway - Ai, Zhongzhu; Yuan, Dongfeng; Cai, Jingyi; Dong, Ruotong; Liu, Wei; Zhou, Daonian (Frontiers in Medicine, 2024)
Background Pruritus ani (PA), a neurofunctional dermatosis, is one of the most common complications of hemorrhoids, which seriously affects the quality of life of patients. Medical hemorrhoid gel (MHG), a product mainly composed of herbal medicine, is widely used for treatment of PA clinically. This study aim to assess the alleviating effect and mechanism of MHG on PA based on rectal epidermis-spinal cord-brain axis using animal models. Methods A chloroquine-induced mouse itching model and a croton oil preparation-induced rat hemorrhoid model were established to evaluate anti-PA effect of MHG. Scratching behaviors of mice were recorded, and histopathology of mice skin and rat ano-rectal tissues was observed through H&E staining. Network pharmacology and western blotting were employed to explore potential mechanism of MHG. Results The study indicated that MHG significantly alleviated chloroquine-induced skin itching and improved pathological injuries in mice skin and rat ano-rectal tissues. Network pharmacology suggested that MHG might regulate the JAK/STAT signaling pathway. Experimental findings showed that MHG significantly downregulated TRPV1 and TRPA1 in rectal tissue, c-Fos and GRPR in spinal cord tissue, and 5-HT1a protein in brain tissue, while upregulating TRPM8 protein in rectal tissue. Furthermore, MHG inhibited the activation of the JAK2/STAT3 signaling pathway in the rectal epidermis-spinal cord-brain axis. Conclusion MHG improves PA by inhibiting the transmission of itching signals in rectal epidermis-spinal cord-brain axis via the JAK2/STAT3 signaling pathway, providing experimental evidence for its clinical application.